2007
DOI: 10.1289/ehp.9282
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Bisphenol A Exposure Induces Preneoplastic Lesions in the Mammary Gland in Wistar Rats

Abstract: BackgroundHumans are routinely exposed to bisphenol A (BPA), an estrogenic compound that leaches from dental materials, food and beverage containers, and other consumer products. Prenatal exposure to BPA has produced long-lasting and profound effects on rodent hormone-dependent tissues that are manifested 1–6 months after the end of exposure.ObjectiveThe aim of the present work was to examine whether in utero exposure to BPA alters mammary gland development and increases its susceptibility to the carcinogen N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
221
0
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 301 publications
(244 citation statements)
references
References 44 publications
12
221
0
7
Order By: Relevance
“…The present report as well as the above-mentioned publications show that developmental exposure to BPA enhances the likelihood of developing carcinomas in both the mammary gland and the prostate [47,48]. Further work will be necessary to verify whether the ductal hyperplasias and CIS we have observed in the mammary gland have the ability to generate invasive carcinomas.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The present report as well as the above-mentioned publications show that developmental exposure to BPA enhances the likelihood of developing carcinomas in both the mammary gland and the prostate [47,48]. Further work will be necessary to verify whether the ductal hyperplasias and CIS we have observed in the mammary gland have the ability to generate invasive carcinomas.…”
Section: Discussionsupporting
confidence: 74%
“…However, the increased propensity of the BPA-exposed animals to develop PINs was revealed when those rats were given a hormonal stimulus (testosterone plus estradiol for 16 weeks) during adulthood. Similarly, Durando et al showed that fetal exposure to 25μg BPA/kg BW/day induced the development of mammary gland neoplasia which was manifested after treatment with NMU during adulthood [48].…”
Section: Discussionmentioning
confidence: 92%
“…The mammary glands of the rats in these studies also had an increase in tumor multiplicity and the number of tumors, indicating that BPA exposure can increase susceptibility to DMBA‐induced mammary cancer. In another study by Durando and colleagues, Wistar rats exposed in utero to a low dose of BPA (25 µg kg –1 BW day –1 ), who received N ‐nitroso‐ N ‐methylurea (NMU, a chemical carcinogen) at PND50, had significantly more hyperplastic ducts at 110 and 180 days of age and had a higher incidence of NMU‐induced ductal carcinoma in situ at 180 days of age 110. These results together suggest that BPA exposure during early life can sensitize the mammary gland to carcinogenic insults encountered in adulthood.…”
Section: Epidemiological Animal and In Vitro Evidence Of Bpa‐associmentioning
confidence: 99%
“…Furthermore, rats exposed to BPA in utero developed precancerous and cancerous lesions (32). Also, perinatal exposure increased rodents' sensitivity to chemical carcinogens (33)(34)(35)(36). Although a small human study found no association between To whom correspondence should be addressed.…”
mentioning
confidence: 99%